(untitled) (The International Journal for Scientific Research, 2025)
The study aimed to analyze the impact of industrial automation on productivity, manufacturing process speed, and error reduction at SPIMACO Pharmaceutical Company. It also sought to assess the role of automation in reducing operational costs and improving resource efficiency, as well as identifying the key challenges facing the implementation of industrial automation at SPIMACO. The research adopted a descriptive-analytical approach due to its suitability for the nature of the study. The study sample consisted of 113 employees from SPIMACO Pharmaceutical Company, selected randomly. A questionnaire was used as the primary data collection tool. The findings revealed that automation significantly contributes to increasing the daily production rate in the factory, with a mean score of (4.00), indicating a high level of agreement on this effect. Industrial automation was found to enhance productivity and accelerate manufacturing processes within the company. Additionally, automation helps reduce raw material consumption by improving process accuracy, with a mean score of (3.27). However, the study also identified challenges in implementing industrial automation. The biggest challenge was the need to retrain and qualify employees to use new technologies, with a mean score of (4.57), highlighting the necessity of intensive training programs to ensure the success of automation. Moreover, companies face difficulties integrating automated systems with older traditional systems, scoring (4.40), which calls for effective integration solutions to facilitate the transition.